GM Crop Coexistence in Practice: Delivering Real Choices for Farmers and Consumers. (April 2016) - Pearsall, Daniel
Summary: The political context which frames the EU policy debate over farm‐level coexistence between genetically modified (GM) and non‐GM crops has progressively lost sight of the practical and commercial realities involved. Instead of providing the basis for farmers and consumers to exercise a meaningful choice in relation to approved GM and non‐GM products, the politically motivated use of disproportionate or unworkable coexistence measures has in itself become a further barrier to GM crop adoption in Europe. Yet coexistence is not a new concept in agriculture, and well‐established practices exist throughout the farm supply chain to produce, segregate, store and deliver harvested crops to specified levels of quality and purity. In each case, the level of market differentiation – not the degree of political prejudice – determines the nature and cost of the segregation procedures applied. This article argues that worldwide experience of managing GM crop coexistence in practice suggests that a supply chain‐based approach to managing GM crop coexistence – rather than Government prescription – offers the most effective solution to servicing differentiated market demands. Abstract : The political context which frames the EU policy debate over farm‐level coexistence between genetically modified (GM) and non‐GM crops has progressively lost sight of the practical and commercial realities involved. Instead of providing the basis for farmers and consumers to exercise a meaningful choice in relation to approved GM and non‐GM products, the politically motivated use of disproportionate or unworkable coexistence measures has in itself become a further barrier to GM crop adoption in Europe.